(untitled) (Revista de Ciências Agroveterinárias, 2023)
Corydoras multiradiatus (Orcés V.1960), commonly called “hog-nosed brochis” and popularly known in Peru as “coridora jumbo” is a species of commercial importance among the Amazonian ornamental fish. It is known that the integrity of the health of aquatic organisms positively increases the production and trade of quality products, however, the opposite negatively affects financial losses and production costs. Among the possible diseases, parasitism stands out, and there is still a lack of information, mainly about metazoans, parasitic species that infect C. multiradiatus. Therefore, this study aimed to identify the species of endoparasite metazoans in C. multiradiatus and evaluate the histological lesions present to provide information to ornamental fish producers about these pathologies. Thirty specimens of C. multiradiatus were collected by fishermen in the municipality of “Belén” in Iquitos, Peru. The results revealed the presence of Tylodelphys sp. and nematode larvae in the intestinal wall and Procamallanus (Spirocamallanus) pintoi (Kohn & Fernandes 1988) present in the intestine. The histopathological analysis of the intestine showed several lesions: necrosis; cell desquamation; infiltration of lymphocytes in the mucosa; transepithelial infiltration of lymphocytes; enterocyte hyperplasia; goblet cell hyperplasia and enterocyte desquamation. The study revealed the presence of endoparasites in C. multiradiatus collected in Iquitos, Loreto-Peru, and a moderate degree of damage caused by histological lesions in the intestine of infected fish. The results of this work will serve the fishermen, collectors and aquarists of the city of Iquitos, who, knowing the endoparasites present in C. multiradiatus and the damage they can cause to the fish, will be able to adopt prophylactic measures in order to guarantee the good condition of the fish for its consequent commercialization at a local, national and international level.